Effect of prodigiosin in biofilm formation of its producing bacterial isolates - Alattar, Nagham Shakir; Tawfeeq, Heba Khaleel; Hasan, Jinan Mohammed (Iraqi Journal of Science, 2025)
Serratia marcescens is gram negative bacteria, an opportunistic and nosocomial pathogen. Some strains possess the ability to produce a pigment called prodigiosin. While numerous studies have explored the antimicrobial properties of prodigiosin produced by S. marcescens against other microorganisms, the effect of prodigiosin on the producing S. marcescens isolates themselves remains unclear and warrants further investigation. Ten isolates of S. marcescens were isolated from 135 wound samples collected from some hospitals in Baghdad city. The isolates were cultured on selective media, identified by further biochemical tests and confirmed by VITEK2 compact system in (7.4%) isolation percentage. Four from the ten isolates were pigment producers. The ability of the bacterial isolates to form biofilm was assessed to the bacterial isolates by microtiter plate method; all isolates were biofilm producers. Prodigiosin’s effect on the biofilm development of the producer isolates of S. marcescens was examined depending on incubation in different temperature (37 and 30ºC) the results revealed reducing in their biofilm layers thickness. DNA was extracted from the four isolates to investigate the presence of four genes (flhD, fimC, bsmA and bsmB) related to the formation of biofilms, the results showed that the four isolates had all four genes (flhD, fimC, bsmA and bsmB). Prodigiosin effect on the expression of four genes was examined and the results showed an up regulation in gene expression in all isolates which indicates a relation between prodigiosin production and biofilm formation in S. marcescens.